2004
DOI: 10.1021/tx049870a
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Pectenotoxin, PTX-12, in Dinophysis Spp. and Shellfish from Norway

Abstract: Two novel pectenotoxins (PTXs) were detected by LC-MS in solid phase extracts of net hauls taken at Flødevigen, Norway, in June 2002 that were dominated by Dinophysis acuminata and Dinophysis norvegica. The new compounds were isolated as minor components from a large collection of a Dinophysis acuta-dominated bloom obtained from Skjer, Sognefjorden, Norway, in October 2002. LC-MS and NMR analyses revealed that the new components, 36S-PTX-12 and 36R-PTX-12, occurred as a pair of equilibrating diastereoisomers d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
92
2
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(102 citation statements)
references
References 17 publications
5
92
2
3
Order By: Relevance
“…Nevertheless, transmission through the food web to heterotrophic species cannot be excluded as the proximal source of this toxin in the larger cell size-fraction. The presence of PTX has been detected in isolated cells of the heterotrophic dinoflagellates Protoperidinium divergens, Protoperidinium depressum, and Protoperidinium crassipes that were previously observed to feed on Dinophysis spp., suggesting that transfer of toxin to these heterotrophs had occurred (Miles et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, transmission through the food web to heterotrophic species cannot be excluded as the proximal source of this toxin in the larger cell size-fraction. The presence of PTX has been detected in isolated cells of the heterotrophic dinoflagellates Protoperidinium divergens, Protoperidinium depressum, and Protoperidinium crassipes that were previously observed to feed on Dinophysis spp., suggesting that transfer of toxin to these heterotrophs had occurred (Miles et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…2) (Miles et al, 2004c). It had been believed that the hydrolysis of the PTXs was an enzymatic process in the digestive glands of shellfish; however PTX-2-seco acid and 7-epi-PTX-2-seco acid were also isolated from Dinophysis acuta .…”
Section: Prorocentinmentioning
confidence: 99%
“…Besides the possible toxic effects of YTX, it has been suggested that YTX may act as a defense against grazers as feeding rates by copepods were significantly reduced in the presence of YTX (Makino et al, 2008). Yessotoxin has been found in bivalves and phytoplankton samples in many places around the world (Paz et al, 2008), with records from Norway (Ramstad et al, 2001;Miles et al, 2004) and the Russian White Sea (Vershinin et al, 2006), indicating a subarctic and arctic occurrence. A future expansion in distribution and an increase in bloom formation potential of toxin producing species such as P. reticulatum will have a significant impact, as marine products are assumed to be of increasing economic importance for Greenland and other arctic and subarctic regions.…”
Section: Introductionmentioning
confidence: 99%